PENGARUH KARAKTERISTIK PSIKOGRAFIS KONSUMEN, SIKAP TERHADAP VIDEO TUTORIAL MAKE-UP, DAN CITRA MERK PADA MINAT BELI - Dela Fransiska A; Ike Janita Dewi (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2018)
This research aims to examine the influence of consumer psychographic characteristics (purchase experience, consumer innovativeness, vanity seeking, and variaty seeking behavior) on attitudes towards makeup tutorial videos, the influence of attitude towards on makeup tutorial videos on brand image and the influence of brand image on purchase interest. Data was collected through a survey on 300 female respondents in Yogyakarta Special Region and Central Java, aged 15-45 years old. Data were analyzed using linear regression analysis. The results showed that purchase experience, vanity seeking behavior, and variety seeking behavior positively effect attitudes towards makeup tutorials video, while consumer innovativenes does not affect attitude towards makeup tutorial video. Attitudes towards makeup tutorials video positively effect brand image and brand image positively effect purchase intention.